Pollen collected by honey bees (Apis mellifera L.) from south of Caldén district (Argentina): botanical origin and protein content - Andrada, Ana C. (2005)
In the south of the Caldén district (Phytogeographical province of Espinal, Argentina) the availability of flowering along with the botanical origin and protein content of pollen harvested by honey bees, was studied. During two apiculture periods (from end August to early January) pollen loads were collected every fortnight using pollen traps. A total of 637.96 g of pollen loads was analysed. From 139 species recorded, only 29 were visited by honey bees. In terms of biomass the contribution of exotic plants was high at the end of the winter (Brassicaceae and Erodium cicutarium); during this period of pollen shortage, honey bees collected spores of Puccinia interveniens. During the spring, the native plants (Condalia microphylla, Chuquiraga erinacea, Discaria americana, Grindelia tehuelches, Larrea divaricata, Prosopis sp., Prosopidastrum globosum and Vicia pampicola) were utilised. Those pollen types of high protein level were collected most intensively.